'Small'-proteoglycan: collagen interactions: Keratan sulphate proteoglycan associates with rabbit corneal collagen fibrils at the 'a' and 'c' bands. Issue 9 (September 1985) - Scott, J. E.; Haigh, M.
Abstract : l. Proteoglycans (PGs) in rabbit corneal stroma and mouse sclera have been stained for electron microscopy with Cupromeronic blue in a critical electrolyte concentration (CEC) mode, with and without prior digestion of the tissue by keratanase or chondroitinase ABC to remove the keratan sulphate (KS) or chondroitin-dermatan sulphates (CS or DS) respectively. 2. Two classes of PGs, located orthogonally to the corneal collagen fibrils at either the 'step' (band 'a' or 'c') or gap zone (band 'd' or 'e') are shown to be KS-PGs or DS-PGs respectively. Four separate and specific PG binding sites on Type I collagen fibrils have thus been identified. 3. Rabbit corneal KS and DS PGs each contain two kinds of PG (Gregory JD, Coster L & Damle SP (1982) J. Biol. Chem.257, 6965–6970). We propose that each 'small' protein-rich PG is associated with a specific binding site on the collagen fibril.